Public policy to address displacement in Mexico - Díaz, J (Refugee Studies Centre, University of Oxford, 2014)
At hearings of the Inter-American Commission on Human Rights in November 2013 on the human rights situation in Mexico, the issue of the internally displaced in particular caught my attention, both due to its current serious level and for its potential impact in the not too distant future.